Neglected heterosecdasticity on foreign direct investment outcomes and employed labor force in South Asia - Khawaja Asif Mehmood; Sallahuddin Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The elemental intend of the study is the clarification on the employment effect of inward Foreign Direct Investment (FDI). The challenges faced by the developing economies, of which South Asia (SA) is not away, in context of the measures to have maximum absorptions of the existing labor force are however easier said than to be done. The study opts four of the big economies of SA for the realization of FDI and employment tie-ups. The data range for 31 year, since start from 1980. It is nevertheless striking to bring into practice the altogether computation of more than one regression equation. To do so, methodology of Seemingly Unrelated Regression (SUR) is used and thereby establishes three salient outcomes: a); FDI is significant in effecting employment, b); FDI effects of employment are moderate, c); FDI tends to have dissimilar direction of effects on the selected countries. At the concluding stage, it is suggested to view sector specific effects of FDI and nevertheless recommended for the righteous channelization of foreign capital for better job enhancement.
Keywords: 330; foreign direct investment; employed labor force; South Asia; gross domestic product; Seemingly Unrelated Regression; Feasible Generalized Least Squares